m6A-binding protein IGF2BP1 promotes the malignant phenotypes of lung adenocarcinoma - Wu, Hansheng; Xu, Haijie; Huang, Shujie; Tang, Yong; Tang, Jiming; Zhou, Haiyu; Xie, Liang; Qiao, Guibin (Frontiers in Oncology, 2022)
Background: As the most common type of lung cancer, lung adenocarcinoma (LUAD) poses a significant threat to the life of patients. N6-methyladenosine modification is the most abundant epigenetic modification and may play an important role in the lung carcinogenesis. IGF2BP1, a newly discovered m6A-binding protein, little is known about its role in LUAD. Methods: Data from TCGA, GEO, Kaplan-Meier Plotter and GEPIA databases were systematically analyzed to access the expression and prognostic value of IGF2BP1 on LUAD. Real-time polymerase chain reaction, western blot and immunohistochemistry were performed to detect the mRNA level and protein level of IGF2BP1 in LUAD tissues and para-carcinoma tissues. Cell functional experiments including cell counting Kit-8 assay, transwell invasion assay, wound healing assay, annexin V-FITC/PI double-staining assay and TUNEL assay were used to access the functions of IGF2BP1 on LUAD cell proliferation, invasion, migration, and apoptosis respectively. The top 50 genes that were positively or negatively related to the expression of IGF2BP1 were identified and pathway enrichment analysis was performed. m6A modification sites within IGF2BP1-related genes were predict by SRAMP. Result: 16 m6A regulators were significantly different expressed in LUAD tissues. IGF2BP1 was upregulated in LUAD tissues comparing to the para-carcinoma tissues. High expression of IGF2PB1 was significantly associated with higher clinical stages and poor prognosis of LUAD patients. Furthermore, our functional experiments indicated that IGF2BP1 facilitated cell proliferation, invasion and migration, while suppressed apoptosis in LUAD. Functional enrichment analysis of IGF2BP1-related genes indicated enrichment in several pathways related to oncogenesis. Additionally, m6A modification sites were detected within IGF2BP1-relative genes. Conclusions: Our findings demonstrated that IGF2BP1 play a contributory role in the development and progression of LUAD. It has the potential to become a prognostic predictor and therapeutic target for LUAD.